CLINICAL CHARACTERISTIC OF SOCIAL PHOBIA OF ADOLESCENTS WITH DANGEROUS PRENOSOLOGICAL PATTERN OF CONSUMPTION OF PSYCHOACTIVE SUBSTANCES - Ponomaryova, V.V. (World of Medicine and Biology, 2012)
As a result of our survey we can state, that social phobia in group of adolescents with dangerous prenosological pattern of consumption of psychoactive substances is characterized by clinical heterogeneity and has two variants: generalized and non-generalized. Structural composition of phobic syndrome is not heterogeneous. Presence of three psychopathological syndromes (astheno-phobic, depressive-phobic and anxious-phobic with massive vegetative displays of anxiety) proves complication of compositional structure of social phobia on syndromal level.
Keywords: social phobia; adolescents; clinicо-psychopathological structure; consumption of psychoactive substances